FeOx/Al2O3 Catalysts for High-temperature Decomposition of N2O Under Conditions of NH3 Oxidation in Nitric Acid Production - Sádovská, Galina; Tabor, Edyta; Bernauer, Milan; Sazama, Petr; Fila, Vlastimil; Kmjec, Tomas; Kohout, Jaroslav; Zaveta, Karel; Tokarova, Věnceslava; Sobalik, Zdeněk (Royal Society of Chemistry, 2018)
The catalytic activity of a series of FeOx/Al2O3 prepared under various conditions was evaluated for high temperature decomposition of N2O (HT-deN(2)O) in a complex gas mixture produced by oxidation of ammonia. Thus the relevant step in the industrial nitric acid production process was simulated. The catalyst stability during long-term exposure (12 days) to reaction conditions relevant to HT-deN(2)O was studied. Both fresh and aged FeOx/Al2O3 exhibited more than 90% conversion of N2O in the 750-900 degrees C temperature range. Structural analysis showed that the prepared FeOx/Al2O3 catalysts contained various proportions of , and alumina phases and up to four individual iron species. In the and Al2O3 phases, well stabilized Fe(iii) in T-d or O-h coordination was identified as the active species in HT-deN(2)O.
FeOx/Al2O3 katalyzátory pro vysokoteplotní rozklad N2O za podmínek oxidace NH3 ve výrobnách kyseliny dusičné
Keywords: FeOx/Al2O3; Catalysis; High-temperature decomposition; N2O; Alumina; Stability; Modification changes; FeOx/Al2O3; Katalýza; Vysokoteplotní rozklad; N2O; Alumina; Stabilita; Změny modifikací